PLTS sebagai Backup Supply pada Plant Hidroponik Nutrient Film Tehcnique (NFT) Berbasis IoT - Asfari Hariz Santoso; Masramdhani Saputra; Faradila Nur Rizqy Hamka (Politeknik Negeri Malang, 2023)
Indonesia is geographically located on the equator, which has very strong solar radiation and high rainfall, making it suitable for farming. Hydroponics is used as a growing medium for planting without using large areas of land by utilizing water and prioritizing the nutritional needs of plants. NFT is a hydroponic method that is easy to implement and is quite effective for plants. However, this method requires a cycle that cannot be stopped, so it requires a pump that must be on all the time. Therefore, a backup supply is needed that can guarantee the availability or continuity of the supply of electricity to the load by using an Automatic Transfer Switch (ATS) which keeps the system running if the PLN goes out by using PLTS and can be monitored and controlled at any time using Internet of things (IoT) technology. ). From the results of trials and analysis carried out that the performance of the system when in automatic mode, that is, when the battery reaches a value of 11.3 Volts, it will switch to the PLN supply. The supply from PLTS will change to PLN's supply automatically with a predetermined time, namely from 09.00 WIB to 15.00 WIB. If PLN experiences a blackout, it will switch to the PLTS source until PLN is back on.